2020
DOI: 10.3389/fpsyg.2020.00719
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Training for Improving Attention Regulation in University Students: Is It Effective? and Do Yoga and Homework Matter?

Abstract: The present study examined the effects of mindfulness training on attention regulation in university students and whether the potential benefits of implementation are influenced by the yoga component of mindfulness-based interventions (MBIs) and/or by MBI homework practice. In a non-randomized trial with pre-and post-assessments, n = 180 university students were allocated to either mindfulness training (experimental groups), awareness activities (active control group), or no training (passive control group). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 73 publications
(113 reference statements)
1
16
0
7
Order By: Relevance
“…En este sentido, se han encontrado artículos que analizan los efectos a nivel psicológico y emocional (estrés, ansiedad, depresión, resolución de conflictos, resiliencia, bienestar, motivación), a nivel de rendimiento académico y dos estudios a nivel fisiológico (inmunología y parámetros cardiovasculares). A nivel general se han encontrado resultados positivos en todos los estudios a excepción de dos que no pudieron concluir mejorías significativas asociadas al entrenamiento en atención plena (Turner, et al, 2020;Wimmer, Bellingrath & Von Stockhausen;.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…En este sentido, se han encontrado artículos que analizan los efectos a nivel psicológico y emocional (estrés, ansiedad, depresión, resolución de conflictos, resiliencia, bienestar, motivación), a nivel de rendimiento académico y dos estudios a nivel fisiológico (inmunología y parámetros cardiovasculares). A nivel general se han encontrado resultados positivos en todos los estudios a excepción de dos que no pudieron concluir mejorías significativas asociadas al entrenamiento en atención plena (Turner, et al, 2020;Wimmer, Bellingrath & Von Stockhausen;.…”
Section: Discussionunclassified
“…Esta varianza entre el número de sujetos es debida principalmente a los diseños de estudio. Mientras que procedimientos arduos como toma de muestras sanguíneas (Turner, et al, 2020) dificultan el reclutamiento de participantes, las autointervenciones con vídeos o similares a distancia o los procedimientos mixtos (presencial y a distancia) facilitan el proceso de investigación y la adherencia (Solhaug, et al, 2016;Wimmer, et al, 2020). Además de lo anterior, las características de los participantes en términos de cultura, rama de estudios y otros, podrían influir en los resultados de las investigaciones (Stevenson, Millings & Emerson, 2019).…”
Section: Muestra Y Duración Del Estudiounclassified
See 2 more Smart Citations
“…Previous studies have shown that both attention and working memory are closely related to students' learning ability and performance (Durbrow et al, 2000;Ayres and Sweller, 2014). Issues surrounding students' attention and working memory are currently attracting more and more attention as topics of research (Rebok et al, 2014;Rode et al, 2017;Wimmer et al, 2020). The question of which psychological or external factors affect attention and working memory has also become a topic of discussion.…”
Section: Introductionmentioning
confidence: 99%